The impact on the skill premium of the task content of jobs: Evidence from online job ads for Chile 2009 - 2018; El impacto del contenido de tareas de los empleos en la prima salarial de trabajadores calificados: Evidencia usando avisos de empleo online en Chile 2009 - 2018 - Jorge Campos-Gonzalez (Estudios de Economía, 2025)
We evaluate the influence on the skill premium of the task content of jobs by exploiting the text data from online job ads covering 2009-2018 (over 189,000 ads) published by one of the leading Chilean online job portals (www.trabajando.com). Our analysis tests the expected complementarity between skilled labour, non-routine cognitive (analytical and interactive), and routine cognitive tasks. Our results show weak evidence of the influence on the skill premium of our task-related measures. Nevertheless, some implications arise from this apparent decrease in the importance of the tasks skilled workers typically perform, such as inefficient educational investment or unwanted changes in the occupational ladder.
Keywords: I26; J23; J24; J31; O15; O33; 330; Task content; Skill premium; Cognitive tasks; Routinisation; Technological change; Skilled labour